ANALISIS ASPEK PEMASARAN DALAM MENINGKATKAN KEPUASAN DAN LOYALITAS PELANGGAN PADA CAFE PERDANA710 DI KOTA MEDAN - Dini Vientiany; Fitri Nabila Hasibuan; Eliza Putri; Annisa Fitri Adina Hutabarat (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Competition in the cafe business in Medan City is getting tighter as the dynamics of urban lifestyles have made cafes both social spaces and recreational areas. This situation requires business actors to design effective marketing strategies to create satisfaction and maintain customer loyalty. This study aims to examine the marketing strategy implemented by Cafe Perdana710 in an effort to increase customer satisfaction and loyalty. The research analysis focuses on the implementation of the 4P marketing mix. The research method used is a descriptive quantitative approach with a survey technique of 60 Cafe Perdana710 customers. Primary data was obtained through questionnaires, while secondary data was obtained from internal business documents and various relevant literature sources. The results of the study show that all elements of the marketing mix, namely product, price, place, and promotion, have a positive influence on the level of customer satisfaction, which in turn contributes to the formation of customer loyalty. Among the four variables, the place and product aspects have the most dominant influence in increasing customer satisfaction and loyalty.